2008
DOI: 10.1007/s00227-008-1031-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and acute phase protein expression in blood samples of harbour seal pups

Abstract: and IL-12 were found at admission, consistent with an activated immune system, whereas the anti-inflammatory cytokine IL-4 was increased before release, suggesting recovery from infections and a mature immune system. This study indicates that cytokines detection is highly sensitive for the status of the immune system of harbor seals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…Metals found in blood of the pups, e.g., Pb or Ni are known sensitizers for harbor seals [9]. Although a direct relationship to metal body burden cannot be shown, investigations of cytokines of harbor seal pups from the German North Sea coast suggest an activated immune system of the newborns directly after collection of the newborns [1,2].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Metals found in blood of the pups, e.g., Pb or Ni are known sensitizers for harbor seals [9]. Although a direct relationship to metal body burden cannot be shown, investigations of cytokines of harbor seal pups from the German North Sea coast suggest an activated immune system of the newborns directly after collection of the newborns [1,2].…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, there is a lack of studies on seal pups. A useful way is the investigation of the newborn and infant pups living in the Seal Centre Friedrichskoog, Germany to get baseline information to health parameters of pups [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…GAPDH has often been used as a normaliser in gene expression studies of seals and fur seals (Sharp et al, 2006;Fonfara et al, 2007Fonfara et al, , 2008, and has been shown to be stable in elephant seals experiencing prolonged fasts Suzuki et al, 2013). Nevertheless, the expression of reference genes can sometimes be influenced by stress or applied treatments, and GAPDH is part of the glycolytic pathway.…”
Section: Methodological Validationmentioning
confidence: 98%
“…Among humans, gene expression profiles are commonly used as biomarkers of diseases or physiological stress (Strand et al, 2005;Abba et al, 2010;Zhou et al, 2012). Genomic responses to different stressors (such as thermal stress) have been reported in marine species (from coral to vertebrate species) under experimental and in situ conditions (Williams et al, 2003;Desalvo et al, 2008;Clark and Peck, 2009), while genes implicated in the immune response to pathogens or pollutants have also been studied in cell cultures as well as in whole organisms such as marine mammals (e.g., Fonfara et al, 2007;Mancia et al, 2007;Fonfara et al, 2008;Lehnert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the selected primer sequences of these proposed bio-markers have already been published for belugas (Sitt et al, 2008;St-Laurent and Archambault, 2000), or for other marine mammal species such as harbor seals and harbor porpoises (Müller et al, 2013;Fonfara et al, 2008). Whenever a published set of primers are not available for belugas, published sequences for cetaceans and other related species were downloaded from GenBank and aligned by using the Clustal Omega software.…”
Section: Total Rna Extractionsmentioning
confidence: 99%